I was discharged from the hospital, now what? The transition of elderly care assisted by family members after covid-19 infection. - Santos, Julia Ferreira (2023)
Coping with the mortality caused by covid-19 has highlighted the elderly population, as this public manifests the most serious changes and repercussions of the respiratory infection process. Therefore, families decided to be closer to their elderly and often ended up becoming their only caregivers, promoting continuity of care in the home environment. Therefore, this work aims to analyze what has been published about transitional care after the period of hospitalization offered by the family caregiver of the elderly during the period of the covid-19 pandemic. The present study is a Systematic Literature Review (SIR). To structure this search, the PICo strategy, EndNote software and Prisma were used. Data collection took place between July and December 2022. The Virtual Health Library (VHL) and PubMed databases were used. The following descriptors, combined with the rounding AND operator, were used: “elderly AND family AND covid-19” and “elderly AND covid-19 AND transitional care”. Inclusion criteria were articles made available free of charge, complete, in Portuguese and English, within a three-year time frame. Five articles were found that addressed the research topic. By categorizing the main findings, the texts address the following points of discussion: overload of family caregivers in the period of the covid-19 pandemic, transitional care as a strategy for continuity of care. The data obtained revealed important contexts to highlight the burden of the family caregiver and the lack of implementation of a care transition strategy for the elderly who were hospitalized due to covid-19. Therefore, it is necessary to transfer knowledge and advances in health and nursing practices, since these are the professionals responsible for training and educating these family members.